2005
DOI: 10.1099/mic.0.27530-0
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic shrinkage of cells of Synechocystis sp. PCC 6803 by water efflux via aquaporins regulates osmostress-inducible gene expression

Abstract: Osmotic stress causes water molecules to efflux from cells through the cytoplasmic membrane. This study reveals that targeted mutation of the aqpZ gene, encoding an aquaporin water channel protein, in the cyanobacterium Synechocystis sp. PCC 6803 prevents the osmotic shrinkage of cells, suggesting that it is the water channel rather than the lipid bilayer that is primarily responsible for water transition through the membrane of this organism. The observations suggest that the aquaporin-mediated shrinkage of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
55
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 27 publications
2
55
0
Order By: Relevance
“…1B), indicating that osmoregulation capacity was exceeded, and cells were no longer able to uphold turgor, and began to leak and shrink when the salinity became too high. The reduction in cell size in response to osmotic stress is known as plasmolysis, and is also widely reported for other bacteria (Koch 1984, Csonka 1989, Shapiguzov et al 2005. The combination of leakage and cell lysis most likely resulted in the high extracellular microcystin concentrations observed at salinities exceeding 10 g l -1 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…1B), indicating that osmoregulation capacity was exceeded, and cells were no longer able to uphold turgor, and began to leak and shrink when the salinity became too high. The reduction in cell size in response to osmotic stress is known as plasmolysis, and is also widely reported for other bacteria (Koch 1984, Csonka 1989, Shapiguzov et al 2005. The combination of leakage and cell lysis most likely resulted in the high extracellular microcystin concentrations observed at salinities exceeding 10 g l -1 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Salt acclimation in cyanobacteria occurs in five phases (Hagemann, 2011). A salt shock causes rapid shrinking of the cells due to loss of water (Blumwald et al, 1983) via aquaporins (Shapiguzov et al, 2005). In the second phase, ions including Na + and Cl 2 passively enter the cells and water flows back to the cells (Reed et al, 1985) but cellular processes including photosynthesis (Allakhverdiev et al, 2000) and gene expression (Hagemann et al, 1994;Fulda et al, 2006) remain slow due to high ion (especially Na + ) content of the cells.…”
mentioning
confidence: 99%
“…Water flux occurs mainly through water-permeable channels, including aquaporins, simultaneously with the transport of ions across the membrane and the change in concentration of the compatible solutes synthesized de novo in the cells. In Synechocystis, it has been reported that very little shrinkage of ⌬aqpZ cells was observed after addition of large amounts of a nonionic compound, sorbitol, to the medium (7,42). Unlike Na ϩ , sorbitol shows very low permeation across the plasma membrane in the cyanobacterium Synechococcus sp.…”
mentioning
confidence: 99%
“…Simultaneously with the transport of ions across the membrane or the change in intracellular concentration of compatible solutes, such as glucosylglycerol, carbamides, polyols, purines, pyrimidines, and glycerol, by de novo synthesis in response to the external salt concentration or osmolarity change, water flux occurs mainly through water-permeable channels called aquaporins (18,19,31,32,39,40,44,47). Synechocystis contains in its genome a single-copy gene encoding an aquaporin homolog, aqpZ (1,7,42). The AqpZ protein resides in the plasma membrane in the cell (1).…”
mentioning
confidence: 99%
See 1 more Smart Citation